Estructuras Mentales en la Sistematización del Conocimiento Científico en Ciencias Sociales (High Rate Consulting, 2025)
The objective of this book is to systematize from practical visions the necessary phases for the development of scientific research processes, fundamentally those required in the elaboration of works leading to degrees in university institutions. It is aimed primarily at students in the final stages of their training processes in undergraduate or fourth level studies, who need a practical guide that allows them to operationalize the knowledge acquired during their studies, particularly those associated with research methodology. In the book, the contents are systematized in response to the mental processes required in each of the phases of research, starting from the main idea and fact of doing science. It is organized based on previous experiences of the authors of each chapter, who as a result of their teaching and research careers have accompanied as advisors or tutors processes of generation of degree works or other types of products materialized in monographs, books, book chapters, papers, articles, among others. Practical cases are referred to as examples that will allow the reader to use the tools required to carry out these processes. It is supported by theoretical references that precede in the precision of essential concepts that must be clear in these processes. Finally, a text is consolidated from a simple and sequential language, in the hope that it will be useful for new researchers who are beginning in these processes.